2011
DOI: 10.1098/rsif.2011.0611
|View full text |Cite
|
Sign up to set email alerts
|

Metallic ions as therapeutic agents in tissue engineering scaffolds: an overview of their biological applications and strategies for new developments

Abstract: This article provides an overview on the application of metallic ions in the fields of regenerative medicine and tissue engineering, focusing on their therapeutic applications and the need to design strategies for controlling the release of loaded ions from biomaterial scaffolds. A detailed summary of relevant metallic ions with potential use in tissue engineering approaches is presented. Remaining challenges in the field and directions for future research efforts with focus on the key variables needed to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
279
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 388 publications
(281 citation statements)
references
References 237 publications
(272 reference statements)
2
279
0
Order By: Relevance
“…Even though it is now well accepted that ion dissolution products of bioactive silicate glasses are able to stimulate osteogenesis, as well as angiogenesis, 6 further detailed investigations are required to find out whether and how the ion release of 45S5 Bioglass Ò -based scaffolds or likewise the surface properties of the scaffold material affect the proliferation and tube formation of HUVECs, as well as the growth factor secretion of cells. Concededly, further in vitro and in vivo investigations are required to generate relevant information on the angiogenic potential of cell seeded 45S5 Bioglass Ò -based scaffolds and other bioactive glass compositions were specific (metal) ions with possible angiogenic effect (e.g., Cu) 6,45 are included in the silicate matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Even though it is now well accepted that ion dissolution products of bioactive silicate glasses are able to stimulate osteogenesis, as well as angiogenesis, 6 further detailed investigations are required to find out whether and how the ion release of 45S5 Bioglass Ò -based scaffolds or likewise the surface properties of the scaffold material affect the proliferation and tube formation of HUVECs, as well as the growth factor secretion of cells. Concededly, further in vitro and in vivo investigations are required to generate relevant information on the angiogenic potential of cell seeded 45S5 Bioglass Ò -based scaffolds and other bioactive glass compositions were specific (metal) ions with possible angiogenic effect (e.g., Cu) 6,45 are included in the silicate matrix.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, more and more evidences show that bioactive ions play important roles in regulating cell behaviors including cell differentiation 11. Some studies have shown that zinc promoted adipogenesis of rat adipocytes and stimulated the conversion of glucose to lipids in 3T3‐L1 fibroblasts and adipocytes in vitro and in vivo,12 suggesting that some bioactive ions indeed can function as stimuli in promoting adipogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, there is a general trend to upgrade properties with some of the well known therapeutical ions because of their biological action [14][15][16]. The development of the three families of glasses was together with an increase of the textural properties (surface area and pore volume) in going from the dense MPGs to the MBGs exhibiting over 500 m 2 /g of surface area and more than 0.5 cm 3 /g of pore volume.…”
Section: Introductionmentioning
confidence: 99%